Gender and the Work of Missionary Translation: Black Women Interpreters among the Jesuits in Seventeenth-Century Cartagena de Indias. - BREWER-GARCÍA, LARISSA (Journal for Early Modern Cultural Studies)
A collection of texts about the Jesuit mission in the Caribbean port of Cartagena de Indias in the seventeenth century describes missionaries' frequent recourse to Black women interpreters to evangelize new arrivals from Western Africa. By analyzing these texts in conversation with Jesuit writings from around the early modern world, this essay demonstrates that the Jesuits in Cartagena employed Black women as interpreters as part of a strategy of accommodation more common to their missions in Asia than Iberian America. To justify their approach in Cartagena, the Jesuits frame Black women interpreters as analogous figures to Jesus's women followers in the New Testament. While the biblical analogies permitted the Jesuits to mention Black women's roles as intercessors in missionary writings, the same figurative language occluded a more specific view of what significance the work of translation might have had for the women themselves and the African new arrivals for whom they interpreted. Reconstructing the context of these portrayals reveals some of the ideological effects of the missionary texts and serves to shed light on the patterns of gendered language used to describe all auxiliary evangelical interpreters throughout Iberian missionary projects in the sixteenth and seventeenth centuries.